Investigating Familial Influence on Stuttering - Triadi, Rai Bagus; Pradianti, Keni; Apriliyani, N Yeffa Afnita (Faculty of Humanities, Universitas Jenderal Soedirman, 2025)
A unique case of stuttering was found in South Tangerang, involving an entire family—both parents and their children—all exhibiting this kind of speech disorder. This study aims to investigate the nature and variation of stuttering experienced by each family member, with a focus on the structural placement of speech disfluencies, the situational conditions under which stuttering occurs, and the potential underlying causes. Employing a qualitative-descriptive research design, data were collected through interviews, direct observation, and stimulus-response techniques. The analysis was conducted through three linguistic lenses: structural (examining the linguistic form and placement of stuttering), cognitive (considering the influence of communicative context and processing load), and psycholinguistic (exploring internal and external causal factors). The findings reveal significant variation in the manifestation of stuttering among family members, with disfluencies occurring at different positions within utterances, affecting their sounds production, such as: 1). losing of several phonemes like /c/, /a/, and /m/; 2). repetitions, and 3). phonemes displacements. In addition, cognitive analysis showed that stuttering is triggered under varying communicative conditions. These findings suggest that both environmental and familial factors may play a significant role in the development and persistence of stuttering. This research contributes to the broader field of stuttering studies by offering new insight into hereditary and contextual influences on speech disorders within the Indonesian cultural and linguistic setting.